Cybervictimization, Depression, and Adolescent Internet Addiction: The Moderating Effect of Prosocial Peer Affiliation - Wang, Zhenhai; Xie, Qi; Xin, Mucheng; Wei, Chang; Yu, Chengfu; Zhen, Shuangju; Liu, Sha; Wang, Jianping; Zhang, Wei (Frontiers in Psychology, 2020)
Although vast research has shown that cybervictimization is a significant risk factor of adolescent internet addiction, little is known about the mediating and moderating mechanisms behind this relationship. The current study examined whether depression mediated the relationship between cybervictimization and adolescent internet addiction, and whether the direct and indirect effect was moderated by prosocial peer affiliation. A sample of 1006 adolescents (Meanage = 13.16; SD = .67) anonymously completed the questionnaires. The results revealed that the positive association between cybervictimization and adolescent internet addiction was mediated by depression. Moderated mediation analysis further showed that prosocial peer affiliation moderated the association between cybervictimization and adolescent internet addiction. However, this indirect effect was stronger for adolescents with high prosocial peer affiliation than for those with low prosocial peer affiliation, which means that the protective effects of prosocial peer affiliation are limited. These findings highlight the mediating and moderating mechanisms between cybervictimization and adolescent internet addiction, and provide guidance for the prevention and intervention in adolescent internet addiction.